Strategi Optimalisasi Pendapatan Asli Daerah Melalui Diversifikasi Sumber Pendapatan di Pemerintah Kota Malang - Riandharu ari pratista; Susi Adelia Putri; Silche Anandis Cahyani; Widya Fismawati; Oktafiana Silvi Ramadhani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the optimization strategy of Local Own-Source Revenue (PAD) of Malang City Government through income source diversification to enhance fiscal independence and sustainable development. The research applies a literature review method, utilizing official government documents, scholarly journals, and relevant regulations. The findings indicate that Malang City's PAD remains heavily reliant on traditional sectors such as hotel and restaurant taxes, parking fees, and market retributions. To address this dependency, the study identifies three key strategies: developing the tourism sector, optimizing the use of regional assets, and digitizing taxation and licensing services. It also highlights implementation challenges, including weak tax administration and low taxpayer awareness. The study contributes by mapping adaptive and sustainable strategic approaches to local financial management, fostering strengthened local fiscal capacity. These findings are expected to provide conceptual and practical foundations for local governments to formulate innovative, equitable, and forward-looking PAD policies in the field of governance and politics.